Virus-Induced Gene Silencing-Based Functional Analyses Revealed the Involvement of Several Putative Trehalose-6-Phosphate Synthase/Phosphatase Genes in Disease Resistance against Botrytis cinerea and Pseudomonas syringae pv. tomato DC3000 in Tomato - Zhang, Huijuan; Hong, Yongbo; Huang, Lei; Liu, Shixia; Tian, Limei; Dai, Yi; Cao, Zhongye; Huang, Lihong; Li, Dayong; Song, Fengming (Frontiers in Plant Science, 2016)
Trehalose and its metabolism have been demonstrated to play important roles in control of plant growth, development and stress responses. However, direct genetic evidence supporting the functions of trehalose and its metabolism in defense response against pathogens is lacking. In the present study, genome-wide characterization of putative trehalose-related genes identified 11 SlTPSs for trehalose-6-phosphate synthase, 8 SlTPPs for trehalose-6-phosphate phosphatase and one SlTRE1 for trehalase in tomato genome. Nine SlTPSs, 4 SlTPPs and SlTRE1 were selected for functional analyses to explore their involvement in tomato disease resistance. Some selected SlTPSs, SlTPPs and SlTRE1 responded with distinct expression induction patterns to Botrytis cinerea and Pseudomonas syringae pv. tomato (Pst) DC3000 as well as to defense signaling hormones (e.g. salicylic acid, jasmonic acid and a precursor of ethylene). Virus-induced gene silencing-mediated silencing of SlTPS3, SlTPS4 or SlTPS7 led to deregulation of ROS accumulation and attenuated the expression of defense-related genes upon pathogen infection and thus deteriorated the resistance against B. cinerea or Pst DC3000. By contrast, silencing of SlTPS5 or SlTPP2 led to an increased expression of the defense-related genes upon pathogen infection and conferred an increased resistance against Pst DC3000. Silencing of SlTPS3, SlTPS4, SlTPS5, SlTPS7 or SlTPP2 affected trehalose level in tomato plants with or without infection of B. cinerea or Pst DC3000. These results demonstrate that SlTPS3, SlTPS4, SlTPS5, SlTPS7 and SlTPP2 play roles in resistance against B. cinerea and Pst DC3000, implying the importance of trehalose and tis metabolism in regulation of defense response against pathogens in tomato.